The devolution of the inheritance management toward the beneficiaries in Klang Valley, Malaysia - MOHAMMAD FIRDAUS ISHAK; MOHD HASROL HAFFIZ ALIASAK; ABDUL HADI NAWAWI; MOHAMAD ISA; SITI FATIMAH HASHIM (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This paper assesses the degree of knowledge regarding the allocation of property management assets upon death in the Klang Valley region of Malaysia. The researcher hopes to identify the root causes of the public’s difficulties with the three estate and property distribution methods recognized by Sharia law: the afraid, the wasiat, and the hibah.Method: Four (4) estate management agencies in Malaysia (Majlis Agama Islam Selangor [MAIS]), As-Salihin Trustee Berhad [ASTB], Amanah Raya Berhad [ARB], and Wasiyyah Shoppe Sdn. Bhd.) were interviewed for this study to collect primary data.Findings: The findings of this study indicate that the procedure of dividing property through inheritance was not carried out because of a lack of understanding regarding inheritance in the community and a lack of knowledge regarding the inheritance of a property that occurred. Problems as large as those affecting the global economy can be exacerbated by a cascade of cases that increase and indirectly withhold assets. To ensure future social and economic relations and to prevent further complexity and confusion in estate management, it is evident that a mechanism must be put into place.Implications/Novel Contribution: Similar to "grant" (donation) and facts in Malaysia, the research is significant because it provides a level of public understanding and information about property management in the event of death.